Investigation of Peritoneal Lavage Cytology before and after Tumor Resection as a Prognostic Factor in Colorectal Cancer - Masayasu Kawasaki; Masao Kameyama; Hirotoshi Kobayashi; Kenjiro Kotake; Kotaro Maeda; Takeshi Suto; Hideki Ueno; Koji Komori; Heita Ozawa; Keiji Koda; Masayuki Ohue; Kenichi Sugihara (Journal of the Anus, Rectum and Colon)
Objectives: There is no consensus on the significance of peritoneal lavage cytology for the prognosis of patients with colorectal cancer. In this prospective multicenter study, we aimed to determine whether positive peritoneal lavage cytology results predict poor patient outcomes and to clarify if the appropriate timing of cytology is before or after tumor resection. Methods: Patients diagnosed with pathological stage II or III colorectal cancer between 2013 and 2017 were enrolled in this study. Peritoneal lavage cytology was performed twice, before and after the tumor resection, and the results were analyzed to determine their effect on prognosis and peritoneal recurrence. Results: We analyzed 1378 patients, and 54 (3.9%) had positive cytology results. Furthermore, 30 patients were positive before tumor resection, 13 after tumor resection, and 11 for both markers. The 5-year relapse-free survival rates (5yRFS) with positive and negative cytology before tumor resection in patients with pStage II were 44.4 and 81.7%, respectively (p=0.0014). The 5-year overall survival rates (5yOS) were 57.1 and 91.6%, respectively (p=0.0046). In Stage III, the 5yRFS and 5yOS between patients with positive and negative cytology did not differ. Patients with positive and negative cytology before tumor resection in pStage II had peritoneal recurrence rates of 11.1 and 1.66%, respectively (p=0.034). These rates were 12.5 and 2.51%, respectively, in patients with pStage III (p=0.011). Conclusions: A positive cytology result before tumor resection is a prognostic factor in Stage II colorectal cancer and is instrumental in predicting peritoneal recurrence in Stages II and III colorectal cancer.